Comparing the Effectiveness of Acceptance and Commitment Therapy and Compassion-Focused Therapy on Psychological Well-Being in Mothers of Children with Educable Intellectual Disability - Gholami Tolmarani, Jamileh; Sharifi, Tayebeh; Kiani, Fariba (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to compare the effectiveness and durability of Acceptance and Commitment Therapy and Compassion-Focused Therapy on psychological well-being in mothers of children with educable intellectual disability.Methods and Materials: The study employed a quasi-experimental pretest–posttest design with a follow-up stage and included two experimental groups and one control group. The statistical population consisted of mothers of students with educable intellectual disability in Lordegan during the 2024–2025 academic year. Using purposive sampling, 45 eligible mothers were selected and randomly assigned to three groups: Acceptance and Commitment Therapy, Compassion-Focused Therapy, and control, with 15 participants in each group. The first experimental group received nine weekly 90-minute sessions of Acceptance and Commitment Therapy, and the second experimental group received eight weekly 90-minute sessions of Compassion-Focused Therapy. The control group remained on a waiting list. Data were collected using Ryff’s Psychological Well-Being Scale at pretest, posttest, and follow-up. Data were analyzed using mixed-design repeated measures analysis of variance and Bonferroni post-hoc test in SPSS version 24.Findings: The results showed a significant main effect of time on psychological well-being, F = 29.60, p = .0001, η² = .413. The interaction effect of time and group was also significant, F = 16.15, p = .0001, η² = .435, indicating that changes in psychological well-being differed significantly across groups. The between-group effect was significant as well, F = 3.96, p = .027, η² = .159. Bonferroni comparisons showed significant differences between Acceptance and Commitment Therapy and Compassion-Focused Therapy, between Acceptance and Commitment Therapy and control, and between Compassion-Focused Therapy and control. The posttest–follow-up difference was not significant, indicating stability of treatment effects.Conclusion: Both interventions significantly improved psychological well-being in mothers of children with educable intellectual disability, but Acceptance and Commitment Therapy demonstrated greater effectiveness than Compassion-Focused Therapy, and the therapeutic gains remained stable at follow-up.